Innovation practice and its performance implications in small and medium enterprises (SMEs) in the manufacturing sector: a resource‐based view - Terziovski, Milé (Strategic Management Journal, 2010)
Abstract Small and medium enterprises (SMEs) in the manufacturing sector make a significant contribution to economic growth, yet most of the research into innovation management in the manufacturing sector has focused on large organizations. This article, however, identifies innovation drivers and their performance implications in manufacturing SMEs. Its study gathered survey data from a sample of 600 Australian SMEs and found that SMEs are similar to large firms with respect to the way that innovation strategy and formal structure are the key drivers of their performance, but do not appear to utilize innovation culture in a strategic and structured manner. This study therefore concludes that SMEs' performance is likely to improve as they increase the degree to which they mirror large manufacturing firms with respect to formal strategy and structure, and to which they recognize that innovation culture and strategy are closely aligned throughout the innovation process. Copyright © 2010 John Wiley & Sons, Ltd.